Epidemiology of congenital diaphragmatic hernia, esophageal atresia, and gastroschisis in South Brazil - Julia Berno Oliveira; Kathleen Russi; Sabrina Kosinski; Gustavo Flacon Shiguihara; Luciano Poliseli; Gabriel Seba; Karina Miura da Costa (EL-Med-Pub, 2023)
Background: Birth defects remain a major contributor to infant mortality and lifelong disabilities. The epidemiology of congenital abnormalities varies around the world and little information is available from Latin America. Methods: This is an epidemiological, descriptive, cross-sectional study with data from the Department of Informatics of the Unified Health System (DATASUS) on Congenital diaphragmatic hernia (CDH), esophageal atresia (EA) and gastroschisis (GS) in South Brazil from 2009 to 2019. Results: The incidence of CDH is 0.93 cases, while EA is 0.47 and GS is 2.87, all per 10,000 live births. There is an association between all the malformations and premature birth, cesarean delivery, low birth weight, and low Apgar scores. Both EA and GS are associated with maternal age, EA with older, and GS with younger mothers. While EA is associated with multiple pregnancies, GS is associated with fewer years of maternal formal education, single parenting, and a lower number of prenatal consultations. CDH is associated with the male sex and black ethnicity. Conclusion: This large population-based study estimates the prevalence and demographic factors associated with CDH, EA, and GS, and extends the limited descriptive epidemiologic information available.